MENINGKATKAN KEDISIPLINAN GURU SMP NEGERI 8 BONTANG DALAM MEMASUKI KELAS PADA JAM PERTAMA MELALUI TEKNIK INDIVIDUAL CONFERENCE - Hj. Sukarsih (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2015)
This study is aimed at increasing teachers’ disciplines to start teaching on time at the first entry job in SMPN 8 Bontang East Kalimantan using individual conference techniques.  The subject of the study is 14 teachers of SMPN 8 Bontang in the academic year 2012/2013.  The study uses three circle conferences each of which involves conversation and setting to explore reasons and commitment. The study discovers that during three weeks with 36 first entry meeting at 07.30-08.40, of 14 teachers involved in the conversation achieved 80%; and 93.% committed to run on time in the first entry job.  Classroom atmosphere is so conducive as teachers are present in the first entry work.